Project Management Roles and Task for Interior Designer During Design Phase - Ahmad Noorhani, Nur Maizura; Mustapha, Arniatul Aiza; Adnan, Hamimah (International Journal of Sustainable Construction Engineering and Technology, 2022)
The interior design process begins with identifying and solving a problem. Good interior design solutions have the power to positively influence people. The process to turn an empty interior into a functionally effective and aesthetically pleasing environment requires a few tasks. The continued misunderstanding of these respective disciplines enables the general public to assume that anyone who creates and furnishes a space with finishes and artworks without a clear understanding of the structural drawings and schematics of that particular space is an interior designer. It is important to ensure that the roles and tasks of an interior designer are not equated to interior decorators and/or interior architects. The aim of the analysis is to validate the importance of project management knowledge in managing interior projects with relation to the professional provision that will improve in Interior design industry needs and expectation from the interior designer towards the knowledge and skills of project management. The objective was to investigate the importance level of interior design professional practices on the Interior design’s task and duties. The quantitative approach was applied in this research to validate the roles and task of interior design project manager in design process of the project. This analysis will demonstrate the significance of a project manager's project management task in an interior design project.